Structure of Nang Gumalunsang Angka Laut Toba Batak Song in Sisolu-Solu Village, North Sumatera - Pintu Batu, Wanda; Wati, Rosmega; Aluna, Aluna (Institut Seni Indonesia Padangpanjang, 2024)
The song 'Nang Gumalunsang Angka Laut' is one of the popular Batak Toba songs that is often performed at certain events such as church services, mourning ceremonies, and entertainment. The research location was in the village of Sisolu-solu, Sumbul District, North Sumatra. The song studied was performed in the SATB choral format and arranged by Mr. Edy Dh Siahaan, S.Th. This research aims to analyze the structure of the choral song titled 'Nang Gumalunsang Angka Laut'. This research uses a qualitative method with a descriptive analysis approach, with the intention of revealing and describing the analysis of the structure of the choral song. The data collection techniques used were observation, interviews, and documentation. The data analysis techniques include data reduction, data presentation, and conclusion drawing. The result of this research is the revealing of the form of the song 'Nang Gumalunsang Angka Laut', which in this research consists of three parts form song , with a melodic line that has similarities (parallel), and has an irregular phrase (more than 4 bars).